SCIENTIFIC AND PEDAGOGICAL FOUNDATIONS OF THE FORMATION OF COGNITIVE COMPETENCIES IN STUDENTS ON THE BASIS OF INNOVATIVE TECHNOLOGIES - Imomova Umida Muzafarovna (Scholar Express Journal, 2023)
This article examines several problems in the formation of cognitive competencies in students, such as studying existing problems in the use of innovative educational technologies and offering solutions to them and analyzing the concepts of implementation of pedagogical innovations and formal and informal forms of teaching of educational technologies
Keywords: Pedagogical process; design; educational need